Gra w karty Króla Zimowego (dziesięciojęzyczna reedycja i facsimile) = Winter King`s Game of Cards (ten language reissue and facsimile) - Šípek, Richard (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Shortly after the Battle of White Mountain, a set of four copperplate prints, each consisting of nine playing cards with allegorical pictures was presumably printed in Vienna. The total print run is unknown. Only two prints of all four copperplates have survived to this day. One in its original uncut form at the Deutsches Spielkartenmuseum in Leinfelden-Echterdingen, Germany.
Keywords: karty do gry; wojna trzydziestoletnia (1618-1648); Fryderyk V (1596-1632); Ferdynand II (cesarz rzymsko-niemiecki; 1578-1637); Troilo, František Gottfried (ok. 1583 - ok. 1648); Dembołęcki, Wojciech (ok. 1575 - między 1645-1647); Lisowczycy; alegoria; literatura okolicznościowa; 17 w.; playing cards; thirty years war; lisovtchics; allegory; occasional literature